2017
DOI: 10.1016/j.dadm.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index in midlife and dementia: Systematic review and meta‐regression analysis of 589,649 men and women followed in longitudinal studies

Abstract: IntroductionWe conducted a meta-analysis of the conflicting epidemiologic evidence on the association between midlife body mass index (BMI) and dementia.MethodsWe searched standard databases to identify prospective, population-based studies of dementia risk by midlife underweight, overweight, and obesity. We performed random-effects meta-analyses and meta-regressions of adjusted relative risk (RR) estimates and formally explored between-study heterogeneity.ResultsWe included 19 studies on 589,649 participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
160
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(185 citation statements)
references
References 84 publications
(266 reference statements)
10
160
2
4
Order By: Relevance
“…We, however, did not find evidence that CBF mediated the relationship between MVRFs and memory performance in midlife that was described previously (Yaffe et al, 2014). The results do not preclude longitudinal relationships, or cerebrovascular reactivity, which was not assessed here, as a potential mediator (Albanese et al, 2017;Tchistiakova & MacIntosh, 2016 , 1996). It is possible that averaging CBF across the ROIs failed to account for regional differences that may be important sources of heterogeneity between participants.…”
Section: Sensitivity Analysescontrasting
confidence: 48%
“…We, however, did not find evidence that CBF mediated the relationship between MVRFs and memory performance in midlife that was described previously (Yaffe et al, 2014). The results do not preclude longitudinal relationships, or cerebrovascular reactivity, which was not assessed here, as a potential mediator (Albanese et al, 2017;Tchistiakova & MacIntosh, 2016 , 1996). It is possible that averaging CBF across the ROIs failed to account for regional differences that may be important sources of heterogeneity between participants.…”
Section: Sensitivity Analysescontrasting
confidence: 48%
“…A systematic review of 580 000 participants in 19 cohorts showed that mid‐life obesity increases the risk of dementia including AD and vascular dementia at older ages. Individuals aged between 35 and 65 with BMI ≥ 30 kg·m −2 have a 23% to 47% higher risk of dementia . A longitudinal study with a 14‐year follow‐up has demonstrated that mid‐life adiposity is associated with β‐amyloid burden, accelerated brain atrophy, and neurodegeneration, accelerating the clinical course of AD .…”
Section: Obesity and Age‐related Diseasesmentioning
confidence: 62%
“…Rather, levels of BMI greater than or equal to 22.5 kg/m 2 (and higher WCs) were associated with a slightly lower dementia risk in later life. Conversely, and in agreement with previous findings, individuals who were categorized as underweight had higher all‐cause dementia risk compared with those with lower‐normal BMI. For vascular dementia, only the highest levels of BMI and WC were associated with increased risk relative to lower‐normal BMI and the lowest fifth of WC.…”
Section: Discussionmentioning
confidence: 93%
“…Rather, individuals with a BMI of greater than or equal to 22.5 kg/m 2 (and higher WCs) had a slightly lower risk of dementia in later life. Conversely, and in agreement with some previous findings, individuals who were categorized as underweight had a one‐quarter greater risk of developing all‐cause dementia compared with those with lower‐normal BMI. When we attempted to exclude those individuals who may have had undetected signs of cognitive impairment at study baseline by excluding the first few years of follow‐up, the relationship remained.…”
Section: Discussionmentioning
confidence: 99%